2015
DOI: 10.1039/c5ra01466b
|View full text |Cite
|
Sign up to set email alerts
|

A DFT/TDDFT mission to probe push–pull vinyl coupled thiophene oligomers for optoelectronic applications

Abstract: VCTO encompassing pull–pull and push–pull categories has been appraised for fine tuning of band gaps and optoelectronic application through DFT/TDDFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 69 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…e position of lobes in L1 at HOMO was localized around six membered ring and LUMO was around five membered ring. Since the lobes of the orbitals are perpendicular to plane of the molecular symmetry, they must be π ⟶ π * transition [18][19][20]. e same type of transition is observed in ZnL1 and CdL1 transitions.…”
Section: Fragmented Fmo Analysismentioning
confidence: 75%
“…e position of lobes in L1 at HOMO was localized around six membered ring and LUMO was around five membered ring. Since the lobes of the orbitals are perpendicular to plane of the molecular symmetry, they must be π ⟶ π * transition [18][19][20]. e same type of transition is observed in ZnL1 and CdL1 transitions.…”
Section: Fragmented Fmo Analysismentioning
confidence: 75%
“…Over the years, the energy levels and frontier molecular orbitals (FMOs) are used to obtain information on the electronic excitation and transition properties of dyes [61,62]. The molecular orbital energy diagrams of HOMO−2, HOMO−1, HOMO, LUMO, LUMO+1, and LUMO+2 are computed at DFT/B3LYP/6-31G(d) in chloroform solvent and depicted in Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oligomers of 1 [2VN] has been designed with the substitution of various donor and acceptor moieties to find candidates which has lower band gap since it's an important attribute in optoelectronic materials. In our earlier work, we investigated the nature of band gap in vinyl substituted thiophene and furan derivatives computationally [9,10]. We observed that, the vinyl coupled furan oligomer tunes the optoelectronic properties to a great extent than the thiophene oligomers since they have lower band gap.…”
Section: Introductionmentioning
confidence: 99%